2021
DOI: 10.1111/odi.13897
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of tongue squamous cell carcinoma: A retrospective cohort study

Abstract: Considering the malignant neoplasms observed in the oral cavity, squamous cell carcinoma (SCC) is the most diagnosed histological type. In 2018, 354,864 new cases of oral cancer were estimated worldwide, with an average of 70% in male patients. In the same year, the number of deaths was 177,384, of which 119,693 occurred in males and 57,691 in females (Bray et al., 2018).According to the National Cancer Institute of Brazil (INCA), considering the oral cavity as the primary location, 11,180 cases in men and 4,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Smokers and drinkers would impair the detoxifying system of GSTs, potentially increasing their susceptibility to carcinogenesis Frontiers in Genetics frontiersin.org (Soares et al, 2017). Many previous studies have shown that tobacco and alcohol are related to HNSC carcinogenesis and reduce the efficacy of tumor-targeted therapy (Jethwa and Khariwala, 2017;da Silva Souto et al, 2021). Multivariate logistic regression further confirmed that T stage and smoker history were independent significant factors of GSTK1 expression.…”
Section: Discussionmentioning
confidence: 65%
“…Smokers and drinkers would impair the detoxifying system of GSTs, potentially increasing their susceptibility to carcinogenesis Frontiers in Genetics frontiersin.org (Soares et al, 2017). Many previous studies have shown that tobacco and alcohol are related to HNSC carcinogenesis and reduce the efficacy of tumor-targeted therapy (Jethwa and Khariwala, 2017;da Silva Souto et al, 2021). Multivariate logistic regression further confirmed that T stage and smoker history were independent significant factors of GSTK1 expression.…”
Section: Discussionmentioning
confidence: 65%
“…Two tumor cell clusters were distinguished based on the expression of the KRT1, KRT4, KRT5, KRT10, KRT13 , and KRT14 genes (Figure 1C). Tumor microenvironment cells were detected as clusters of TAFs and lymphoid and myeloid immune cells (Figure 1B, 1C). Two clusters were mixed with fibroblasts (“tumor + TAFs”) and lymphoid cells (“tumor 3 + lymphoid cells”; Figure 1B, 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Tumor microenvironment cells were detected as clusters of TAFs and lymphoid and myeloid immune cells (Figure 1B, 1C). Two clusters were mixed with fibroblasts (“tumor + TAFs”) and lymphoid cells (“tumor 3 + lymphoid cells”; Figure 1B, 1C). Next, we focused on tumor and immune cell types as key players in tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Tongue squamous cell carcinoma (TSCC) is the most common malignancy in oral cavity (1). Despite improvements in diagnostic tools and treatment modalities, the mortality rate of TSCC has not diminished in recent years and 5-year survival rate for TSCC is still below 50% (2,3). Tumor-node-metastasis (TNM) staging system of the American Joint Committee on Cancer (AJCC) is the most commonly used method to determine treatment modalities and to predict patient prognosis.…”
Section: Introductionmentioning
confidence: 99%